2022
DOI: 10.3389/fphar.2022.959321
|View full text |Cite
|
Sign up to set email alerts
|

LTT and HLA testing as diagnostic tools in Spanish vancomycin-induced DRESS cases: A case-control study

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe T-cell-mediated off-target adverse reaction. DRESS cases caused by vancomycin have often been reported. The HLA-A*32:01 allele has been associated with genetic susceptibility to vancomycin-induced DRESS in US citizens of European descent. We have analyzed the association of the HLA-A*32:01 allele in 14 Spanish DRESS cases in which vancomycin was suspected as the culprit drug, and the lymphocyte transformation test (LTT) as an in vitro as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…It has been calculated as 20% for HLA-A*32:01 in North American patients of European descent with vancomycin-induced DRESS [ 203 ]. However, considering the prevalence of the disease among European patients and the average carriage rate of HLA-A*32:01 at 5%, a lower PPV is likely more realistic [ 221 ] and consistent with the results recently reported in Spanish patients [ 164 ].…”
Section: Etiologic Diagnosis: Identification Of the Culprit Drugsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been calculated as 20% for HLA-A*32:01 in North American patients of European descent with vancomycin-induced DRESS [ 203 ]. However, considering the prevalence of the disease among European patients and the average carriage rate of HLA-A*32:01 at 5%, a lower PPV is likely more realistic [ 221 ] and consistent with the results recently reported in Spanish patients [ 164 ].…”
Section: Etiologic Diagnosis: Identification Of the Culprit Drugsupporting
confidence: 86%
“…In this study, higher sensitivity (S) and specificity (Sp) values were found for determined groups such as anticonvulsants (S 100%, Sp 100%), anti-TB drugs (S 87.5%, Sp 100%), and beta-lactam antibiotics (S 73%, Sp 100%). A recent study determined 91% sensitivity, 91.67% specificity, 91% PPV, and 91.67% NPV for the LTT with vancomycin performed in 14 vancomycin-induced DRESS cases and 12 vancomycin-tolerant control donors [ 164 ].…”
Section: Etiologic Diagnosis: Identification Of the Culprit Drugmentioning
confidence: 99%
“…HLA-A*32:01 is associated with vancomycin-induced DRESS in European population ( Konvinse et al, 2019 ). Bellon et al (2022) also revealed the association between HLA-A*32:01 and vancomycin-induced DRESS in Spanish population. Recently, we reported the association between HLA-A*32:01, HLA-B*07:05, HLA-B:40:06, HLA-B*67:01 and vancomycin-induced DRESS in Taiwanese population ( Wang et al, 2022c ).…”
Section: Hla Susceptibility To Drug-induced Scarmentioning
confidence: 73%
“…Moreover, HLA-B*13:01 testing is recommended for Chinese patients with leprosy before initiating dapsone therapy ( Liu et al, 2019 ). Owing to the relatively high frequency of HLA-A*32:01 in European population, genetic examination before vancomycin treatment can be effective to prevent vancomycin-induced DRESS ( Rwandamuriye et al, 2019 ; Bellon et al, 2022 ). Hama et al (2022) reported that the frequency of HLA-A*32:01 is 6.8% in European population and 20% of whom developed vancomycin-induced DRESS.…”
Section: Application Of Hla Testing In Clinical Practicementioning
confidence: 99%
“…A strong HLA − A ∗ 32 : 01 association was previously reported in patients with European background living in North America who developed vancomycin-induced DRESS [ 26 ]. In a Spanish study on 14 patients with DRESS, HLA − A ∗ 32 : 01 was found in 36% of cases [ 27 ]. Furthermore, the lymphocyte transformation test (LTT) showed high sensitivity and specificity in cases of vancomycin-induced DRESS.…”
Section: Discussionmentioning
confidence: 99%